Lichen Planus Induced by Pegylated Interferon Alfa-2a Therapy in a Patient Monitored for Delta Hepatitis - Safak Kaya; Eyup Arslan; Birol Baysal; Sule Nergiz Baykara; Ozlem Ceren Uzun; Sehmuz Kaya (Case Reports in Infectious Diseases)
Interferons are used for treatment of chronic hepatitis B. They can induce or exacerbate some skin disorders, such as lichen planus. In this study, as we know, we presented the first case developing lichen planus while receiving interferon treatment due to delta hepatitis. A 31-year-old male patient presented to our outpatient clinic with HBsAg positivity. With his analyses, HBV DNA was negative, anti-delta total was positive, ALT was 72 U/L (upper limit 41 U/L), and platelet was 119 000/mm3. He was therefore started on subcutaneous pegylated interferon alfa-2a therapy at 180 mcg/week for delta hepatitis. At month 4 of therapy, the patient developed diffuse eroded lace-like lesions in oral mucosa, white plaques on lips, and itchy papular lesions in the hands and feet. Lichen planus was considered by the dermatology clinic and topical treatment (mometasone furoate) was given. The lesions persisted at month 5 of therapy and biopsy samples were obtained from oral mucosal lesions and interferon dose was reduced to 135 mcg/week. Biopsy demonstrated nonkeratinized stratified squamous epithelium; epithelial acanthosis, spongiosis, and apoptotic bodies were observed in the epidermis and therefore lichen planus was considered. At month 6 of therapy, lesions did not improve and even progressed and interferon treatment was therefore discontinued.